Assessing exogenous carbohydrate intake needed to optimize human endurance performance across sex: insights from modeling runners pursuing a sub-2-h marathon - Lukasiewicz, C. J.; Vandiver, K. J.; Albert, E. D.; Kirby, B. S.; Jacobs, R. A. (Journal of Applied Physiology, 2024)
Carbohydrate (CHO) availability sustains high metabolic demands during prolonged exercise. The adequacy of current CHO intake recommendations, 30-90 g·h-1 dependent on CHO mixture and tolerability, to support elite marathon performance is unclear. We sought to scrutinize the current upper limit recommendation for exogenous CHO intake to support modeled sub-2-h marathon (S2M) attempts across elite male and female runners. Male and female runners (n = 120 each) were modeled from published literature with reference characteristics necessary to complete a S2M (e.g., body mass and running economy). Completion of a S2M was considered across a range of respiratory exchange rates, with maximal starting skeletal muscle and liver glycogen content predicted for elite male and female runners. Modeled exogenous CHO bioavailability needed for male and female runners were 93 ± 26 and 108 ± 22 g·h-1, respectively (P < 0.0001, d = 0.61). Without exogenous CHO, males were modeled to deplete glycogen in 84 ± 7 min, females in 71 ± 5 min (P < 0.0001, d = 2.21) despite higher estimated CHO oxidation rates in males (5.1 ± 0.5 g·h-1) than females (4.4 ± 0.5 g·h-1; P < 0.0001, d = 1.47). Exogenous CHO intakes = 90 g·h-1 are insufficient for 65% of modeled runners attempting a S2M. Current recommendations to support marathon performance appear inadequate for elite marathon runners but may be more suitable for male runners in pursuit of a S2M (56 of 120) than female runners (28 of 120).